THE RELATIONSHIP BETWEEN DIET AND CHOLESTEROL INCIDENCE IN THE WORKING AREA OF THE LAGEUN HEALTH CENTER, SETIA BAKTI SUB-DISTRICT, ACEH JAYA DISTRICT YEAR 2023/2024 - Amin, Muslim; Silvany, Novriza (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2023)
One of the current issues is the increasing incidence of non-communicable diseases, influenced by changes in lifestyle, including high cholesterol. Cholesterol is a complex fat compound, with 80% produced endogenously and 20% derived from dietary sources. Foods high in cholesterol typically come from animal products such as egg yolks, meat, liver, and brain. This research employs a quantitative approach with descriptive analysis. The data used in this study are sourced from previous journals. Data collection involved using questionnaires to educate the community in Lhok Buya village about cholesterol, aiming to enhance their knowledge. A total of 35 respondents participated, predominantly female (31 respondents, 88.6%), with male respondents numbering 4 (11.4%). The respondents were categorized into three age groups: Adolescents (12-25 years) with 6 respondents (17.1%), Adults (26-45 years) with 18 respondents (51.4%), and the Elderly (46-65 years) with 11 respondents (31.4%). Following the educational intervention, most respondents (85.7%, or 30 individuals) demonstrated good knowledge about cholesterol, while a minority (14.3%, or 5 individuals) exhibited less understanding.